Beyond bits: The future of quantum information processing - Steane, A; Rieffel, E (IEEE, 2000)
Quantum information theory seeks to unite some of the most influential ideas of 20th century science: quantum mechanics, computer science and information theory. The development of quantum information theory has only begun, and only a few applications are known, mostly in quantum system control and data security. The future of the theory is hard to predict, but it seems poised to contribute to some of the most exciting ideas of the 21st century. This theory gives an ideal framework for developing a better understanding of how nature works and what it will allow to be done.